INFLUENCE OF TRAINING AND DEVELOPMENT PRACTICES ON THE PERFORMANCE OF NON-GOVERNMENT ORGANIZATIONS. A CROSS-SECTIONAL STUDY OF TASO MBARARA. - ATUKWATSE, SHARON; Mwesigye, Jimmy; Begumisa , Benard (Student’s Journal of Health Research Africa, 2024)
Background. Human Resource Management practices are functions and practices of human resources such as recruitment and selection, skills monitoring and training, and ongoing performance management of businesses to ensure improved Organizational performance. The study aims to determine the influence of training and development practice on organizational performance. Methodology. A sectional study used both quantitative and qualitative research approaches. Using a simple random sampling technique 132 respondents were selected from TASO Mbarara comprising human resource managers from Ankole Cluster, MEAL officers, MEAL managers, HR department staff, and top management. Pearson correlation, multiple regression analysis, and t-test statistics were used to establish relationships between independent and dependent variables. Results. The majority of 80 (69%) respondents in the study were males whereas 36 (31%) were females A Pearson correlation coefficient of 0.726 showed a positive and significant relationship between Training and Development Practices. The findings were important at a 0.000 level given that Training and Development Practices is statistically significant at a 95% confidence level since a sign value of 0.000 is less than 0.05. The coefficient of determination (Adjusted R Square) is 0.280. This implies that Training and Development Practices account for 28% of the variations in the Organisational Performance of TASO Mbarara A simple linear regression analysis using the standardized coefficients for Training and Development Practices indicated a beta standardized coefficient value of 0.726, with p-value = 0.000 Meaning that Training and Development Practices has a positive and significant effect on Organizational performance of TASO Mbarara. Conclusion. Training and development practices are part of the significant practices that contribute to the better organizational performance of TASO Mbarara. Recommendations. TASO needs to conduct compliance training for all staff to ensure understanding and adherence to HR policies and improved performance.